Synthesis of Zn2SnO4 octahedron with enhanced H2S gas-sensing performance. (1st September 2018) - Xu, Ting-Ting; Zhang, Xian-Fa; Deng, Zhao-Peng; Huo, Li-Hua; Gao, Shan
Graphical abstract: Zn2 SnO4 octahedra were prepared through a facile hydrothermal method followed by calcination in air atmosphere. The fabricated sensor shows excellent selectivity and sensitivity to H2 S at lower temperature of 170 °C. The response to 100 ppm H2 S can reach up to 172.5 and the lowest detection limit is down to 5 ppb. Such outstanding gas properties indicate that the Zn2 SnO4 octahedra could be utilized as promising sensor material for detecting ppb-level H2 S. Abstract: Zinc stannate (Zn2 SnO4 ) that used for detecting traces of H2 S was less concerned. In this work, Zn2 SnO4 octahedra with the average size of 0.18 μm were prepared through a facile hydrothermal method followed by an annealing process in air atmosphere. The fabricated sensor shows excellent selectivity and sensitivity to H2 S at working temperature of 170 °C. The gas response exhibits good linear relationship with the increasing of concentrations in the range of 5 –10 ppm. The response to 100 ppm H2 S can reach up to 172.5 and the lowest detection limit is down to 5 ppb. Such outstanding gas property might be attributed to the morphology of the octahedra and the increased contact area between Zn2 SnO4 and target gas, which may has potential applications in detecting traces of H2 S.